A Surgical Resident's Perspective about COVID-19 Pandemic: Unique Experience and Lessons Learnt - Madhuri Chaudary; Prakash Kumar Sasmal (University Library System, University of Pittsburgh, 2020)
Discussion Points. • Experience of a surgical trainee to manage COVID-19 patients along with surgical emergencies. • In spite of managing high-risk seropositive cases during non-COVID-19 times with impunity, there is always a sense of apprehension during operation in this critical time. • E-learning is promoted presently with online seminars and webinars on managing COVID-19 and other non-COVID-19 diseases, which is overall a new experience during this critical time. • Every nation and medical university needs to adequately increase the infrastructure to tackle the similar situation and also train their future generation of health care providers more broadly at least to manage critically ill patients during epidemics, irrespective of subspecialties. • The global community should unite to fight against this invisible enemy of humanity.